1999
DOI: 10.1016/s0006-3223(98)00252-2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment of seasonal affective disorder (SAD) by using light visors: bright white or infrared light?

Abstract: Light visors can be effectively used to prevent the development of SAD. The fact that exposure to infrared light was as effective as exposure to bright white light questions the specific role of visible light in the treatment of SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…The effects of treatment do not persist after discontinuation of BLT, thus a relapse can be anticipated few days after stopping the treatment. Some SAD patients may profit from a prophylactic initiation of BLT [144,145] . In this context, psycho-educational training for the detection of early symptoms (difficulties in awakening, daytime fatigue and carbohydrate craving) may help to prevent the onset of a full-blown episode of SAD.…”
Section: Administrationmentioning
confidence: 99%
“…The effects of treatment do not persist after discontinuation of BLT, thus a relapse can be anticipated few days after stopping the treatment. Some SAD patients may profit from a prophylactic initiation of BLT [144,145] . In this context, psycho-educational training for the detection of early symptoms (difficulties in awakening, daytime fatigue and carbohydrate craving) may help to prevent the onset of a full-blown episode of SAD.…”
Section: Administrationmentioning
confidence: 99%
“…The placebo effect is hardly controlled in bright light studies (for more detail see Eastman 1990;Bouhuys et al 1994;Meesters et al 1999;Putilov & Danilenko, in press;Putilov et al 1999Putilov et al , 2005. In particular, the problem is that the difference between presumably less and more effective treatments (i.e.…”
Section: Explanation Of Antidepressant Effectsmentioning
confidence: 99%
“…Richter et al 1992;Meesters et al 1993Meesters et al , 1999. The comparison of SAD patients with patients without seasonality in terms of the five-factor model of personality (Bagby et al 1996) revealed the significant difference on one of five dimensions: they scored higher than non-SAD patients on the openness dimension.…”
Section: Explanation Of the Effect Of Seasonality On Antidepressant Rmentioning
confidence: 93%